Edible Insects as New Food Frontier in the Hospitality Industry - Ayieko, Irene A.; Onyango, Maria; Ngadze, Ruth T.; Ayieko, Monica A. (Frontiers in Sustainable Food Systems, 2021)
Entomophagy has led to the recognition of insects as playing a major role in improving global environmental health, food and nutritional security. The processing methods have shown to greatly affect its acceptance and consumption. This review selectively summarizes the current trends related to consumption of edible insects among householders, the food and beverage industry consumers, and its prospects as a key attractant in tourism destinations. Its’ unconventional processing techniques have hindered its growth especially in the food business industry, thus influencing the food value chain in entomophagy. The paper reviews perceptions on insects’ consumption by identifying already developed processing methods, emphasizing on the health benefits of entomophagy and its economic importance. A structured literature search is conducted to identify published studies on edible-insects product processing, food design, its acceptance and consumption in the food industry. The literature search is focused on its acceptance as whole consumption or after product development and whether it can be accepted in the food industry in its new form. It was observed that Europe has the highest publications on acceptance, public perception, processing technology and research trends. Africa tends to prefer whole consumption, as the Americans is still have not taken a stand. Results reveal that processing of the insects and incorporating other ingredients have greatly increased acceptance of edible insects. Therefore, we conclude that new food designs that incorporate insects as special ingredient should be promoted in main stream hotels to attract food and culture tourism.